New Zealand pumicite as a precursor in producing alkaline cement with aluminate-based activators - Roohollah Kalatehjari; Elmira Khaksar Najafi; Afshin Asadi; Martin Brook (Case Studies in Construction Materials)
This study investigates the activation of New Zealand pumicite (pumice powder) using sodium aluminate (NaAlO₂) solution, both alone and in combination with 10 M KOH solution, at various weight ratios of 1, 3, and 5, to produce alkali-activated cement. Compressive strength tests and microstructural analyses were conducted to assess the effects of activator/precursor ratios, activator type, aging time, and curing temperature (65°C for 72 hours or room temperature). The internal porosity of the pumicite played a key role in aluminosilicate phase dissolution and mobility, resulting in similar compressive strengths across different ratios. NaAlO₂ alone achieved compressive strengths of 60 MPa and 67 MPa after 4 and 65 days, respectively, while the binary solutions showed reduced strength with increased aging. Room temperature curing required almost three times the aging period to match the 28-day compressive strengths achieved after curing at 65°C for 72 hours. Microstructural analyses revealed that NaAlO₂ solution adjusted the Si/Al ratio, forming high-Al and high-Si gels as well as zeolite-A, underscoring its benefits. This study demonstrates the potential of using locally sourced New Zealand pumicite as a precursor in alkali-activated cement, particularly in regions lacking traditional industrial by-products.